Plurality of pluralism - Echeverría, Javier (Estudios de Filosofía, 2008)
The contrast between pluralism and monism has been raised many times throughout the history of philosophy. This debate has had several facets. My purpose in this contribution is to evoke this variety of aspects, in order to propose some arguments in favor of pluralism in philosophy. [Fragment]